Islamic Counseling Guidance Islamic Counseling Guidance As A Teenage Social Conflict Resolution In Madrasah - Failasufah Failasufah; Farida Hanum; Mohamad Hilmi Bin Mat Said (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2022)
This study aims to describe Islamic counseling guidance as conflict resolution carried out to help alleviate conflict problems and packaged as a psychological therapy procedure, becoming a strategic way that can be applied to resolve conflicts among adolescents, increase anti-violent and hostile behavior, and increase the use of resolution strategies. peaceful conflict. Conflict is a form of interaction between humans who have interests between the two, can be in the form of conflict, bickering, threats, or others with the aim of destroying the opponent. The method used in this study is qualitative. The results showed that, the occurrence of social conflicts among adolescent students in madrasas, conflicts experienced by adolescent students in madrasas began with the emergence of several students whose numbers were less than one percent of the number of students in madrasas involved in social groups or gangs. who act in the name of the “school gang” with all their activities, such as ngre-se or klitih, hanging out, fights, convoys, which occur because of the interests of social groups of adolescent students to show their existence. As a preventive and problem solving step, Islamic counseling guidance services as a conflict resolution aim to assist adolescent students in resolving conflict problems in peaceful ways. Keywords: Islamic counseling guidance, conflict resolution, and conflict